The Influence of Perceived Ease of Use, Perceived Price Value of Bundling Promotion, and Perceived Attractiveness of Original Contents on Disney+ Hotstar Subscription Intention - Muhammad Fadhel Raditya; Tandiyo Pradekso; Hapsari Dwiningtyas Sulistyani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
Disney+ Hotstar as a technology-based paid movie streaming service, of course, is required to have and create a feeling of ease while using the services offered for its users. The experience in question is that the application can be used easily and can meet the expectations of convenience for its users, as well as being able to access available content without network or advertising barriers. In addition, Disney+ Hotstar also uses several strategies to increase sales and build buyer interest to then subscribe to Disney+ Hotstar. One of them is Disney+ Hotstar in collaboration with Telkomsel to create a bundling product, where buyers can purchase packages that include a Disney+ Hotstar subscription, as well as quotas to enjoy the available services. Disney+ Hotstar also then produces original content that is considered to be able to attract the attention of potential Disney+ Hotstar customers. These original contents are only available on Disney+ Hotstar, and can only be enjoyed by Disney+ Hotstar subscribers. However, several surveys conducted in 2021 show that Disney+ Hotstar is still behind its competitors in the SVOD market. This study aims to explain the effect of perceived ease of use, perceived price value of bundling promotions, and perceived interest in original content on interest in subscribing to Disney+ Hotstar. The theory used in this study is the Extended Unified Theory of Acceptance and Use of Technology (UTAUT2), with a sampling technique in the form of non-probability sampling. The sample is 100 people with 1 characteristics of active SVOD users and Telkomsel users aged 18-34 years, and have never subscribed to Disney+ Hotstar before. The results of hypothesis testing with multiple regression techniques show that there is no effect of perceived ease of use, perceived price value, and perceived content interest on buying interest with a significance value of (0.083). This shows that perceived ease of use, perceived price value, and perceived content interest have no simultaneous effect on respondents' intention to subscribe to Disney+ Hotstar.